2022
DOI: 10.3390/su141811176
|View full text |Cite
|
Sign up to set email alerts
|

Wood from Forest Residues: Technological Properties and Potential Uses of Branches of Three Species from Brazilian Amazon

Abstract: Branch wood presents potential volumetry that may have several applications, and its use may improve forest management efficiency in the Amazon. However, there is a lack of knowledge regarding the properties of branch wood when compared to the stem or what its potential applications might be, considering the possible variability of wood formation in branches. This study aimed to characterize physically and mechanically the branch wood of Dipteryx odorata, Hymenolobium petraeum and Hymenaea courbaril and to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
1
0
1
Order By: Relevance
“…Therefore, the use of residues from the primary and secondary processing of tropical wood and the study of these species in panel production can provide subsidies for the installation of OSB factories in the Amazon region [18]. As an example, a study carried out using tropical wood residues demonstrated the potential use of residues for non-structural purposes, furniture, tools, and panels composed of short pieces [21]. Developing materials made of forest biomass by-products can be a viable alternative for replacing conventional materials, in addition to showing the potential for waste reuse [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of residues from the primary and secondary processing of tropical wood and the study of these species in panel production can provide subsidies for the installation of OSB factories in the Amazon region [18]. As an example, a study carried out using tropical wood residues demonstrated the potential use of residues for non-structural purposes, furniture, tools, and panels composed of short pieces [21]. Developing materials made of forest biomass by-products can be a viable alternative for replacing conventional materials, in addition to showing the potential for waste reuse [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…É importante frisar que em função das dimensões relativamente pequenas das lamelas externas, a viabilidade de utilização de madeiras nativas de alta resistência para compor esses elementos estruturais se justifica ainda se consideramos a grande quantidade de madeiras de galhos dessas espécies é deixada na área de manejo durante a colheita florestal. Estima-se que de 2009 até 2015, cerca de 900,000 m³ de madeiras nobres foram abandonados nas áreas de manejo madeireiro (MOREIRA et al, 2022). A utilização dessa matéria prima para reforço de elementos estruturais representaria uma forma de melhorar o rendimento da colheita de madeira na região amazônica.…”
Section: Peso Específico Das Peçasunclassified